Electrocatalytic water oxidation reaction promoted by cobalt-Prussian blue and its thermal decomposition product under mild conditions. Issue 45 (5th November 2020) - Zambiazi, Priscilla J.; Aparecido, Gabriel de O.; Ferraz, Thiago V. de B.; Skinner, William S. J.; Yoshimura, Rafael G.; Moreira, Daniel E. B.; Germscheidt, Rafael L.; Nascimento, Lucas L.; Patrocinio, Antonio Otavio T.; Formiga, André L. B.; Bonacin, Juliano A.
Abstract : Water oxidation studies with Co-Prussian blue and Co3 O4 . Figure adapted from 'Under the Wave off Kanagawa' (Kanagawa oki nami ura), also known as 'The Great Wave', from the series 'Thirty-six Views of Mount Fuji' ('Fugaku sanjūrokkei') by K. Hokusai. Abstract : Cobalt-Prussian blue analogues are remarkable catalysts for the oxygen evolution reaction (water oxidation) under mild conditions such as neutral pH. Although there are extensive reports in the literature about the application of these catalysts in water oxidation (the limiting step for hydrogen evolution), some limitations must be overcome in terms of improving the turnover frequency, oxygen production, long term stability, and elucidation of the mechanism. Another important feature to consider is the industrial processability of electrolytic cells for water splitting. For these reasons, we have reported herein a comparison of the electrochemical and chemical properties of three catalysts produced from cobalt-Prussian blue. Co–Co PBA 60 refers to cobalt-Prussian blue heated up to 60 °C with a high content of water. Co–Co PBA 200 is the same starting material but heated up to 200 °C with a low water content. Finally, Co3 O4 is a thermal decomposition product obtained from heating cobalt-Prussian blue up to 400 °C. Although Co–Co PBA 60 has a higher overpotential for water oxidation than Co–Co PBA 200, this catalyst is kinetically faster than Co PBA 200. It is suggested that the water coordinated to Co 2+ in Co–Co PBA 60 can accelerate the reaction and that there is a balance between the thermodynamic and kinetic characteristics for determining the final properties of the catalyst at pH = 7. Another important observation is that the Co3 O4 catalyst has the best performance among the considered catalysts with the highest TON and TOF. This suggests that the different mechanisms and surface effects demonstrated by the Co3 O4 catalyst are more conducive to efficient water oxidation than those of Prussian blue. Further studies concerning the effect of water and surface on these catalysts under mild conditions are essential to gain a better understanding of the mechanism of water oxidation and to advance the development of new catalysts.